Uptake of Plasmodium falciparum Gametocytes During Mosquito Bloodmeal by Direct and Membrane Feeding - Talman, Arthur M.; Ouologuem, Dinkorma T. D.; Love, Katie; Howick, Virginia M.; Mulamba, Charles; Haidara, Aboubecrin; Dara, Niawanlou; Sylla, Daman; Sacko, Adama; Coulibaly, Mamadou M.; Dao, Francois; Sangare, Cheick P. O.; et al. (Frontiers in Microbiology, 2020)
Plasmodium falciparum remains one of the leading causes of child mortality, and nearly half of the world’s population is at risk of contracting malaria. While pathogenesis results from replication of asexual forms in human red blood cells, it is the sexually differentiated forms, gametocytes, which are responsible for the spread of the disease. For transmission to succeed, both mature male and female gametocytes must be taken up by a female Anopheles mosquito during its blood meal for subsequent differentiation into gametes and mating inside the mosquito gut. Observed circulating numbers of gametocytes in the human host are often surprisingly low, yet even sub-patently infected carriers are able to transmit malaria. A pre-fertilisation associative behaviour has been hypothesised to explain the efficiency of human-to-mosquito transmission but has not been sufficiently tested due to a lack of appropriate tools. In this study, we describe the optimisation of a qPCR tool that enables the relative quantification of gametocytes within very small input samples. Such a tool allows for the quantification of gametocytes in different compartments of the host and the vector that could potentially unravel mechanisms that enable highly efficient malaria transmission. We demonstrate the use of our gametocyte quantification method in mosquito blood meals from both direct skin feeding on Plasmodium gametocyte carriers and standard membrane feeding assay. Relative gametocyte abundance was not different between mosquitoes fed through a membrane or directly on the skin suggesting that there is no systematic enrichment of gametocytes picked up in the skin.